The Methodological Algorithm of Forming Multimedia Foreign Language Communicative Competence of Secondary School Students - Akmaral Rakhman; Dana Shayakhmetova; Zhanar Kulekenova; Elmira Gerfanova; Aliya Ayazbayeva (Qubahan Academic Journal)
This article is dedicated to one of the most pressing topics in modern foreign language education, the problem of forming multimedia foreign language communicative competence of secondary school students. This scientific phenomenon can be constituted as a cumulative readiness and ability of a multilingual learner to effectively engage in foreign language communication within the context of multimedia-mediated intercultural communication, aimed at self-development and self-realization of its participants through conscious and active assimilation of new social experience. At the core of the structure of this competence lies a set of universal learning actions that ensure the students’ ability for self-development and self-improvement through conscious and active assimilation of new social experience. The study identifies a structured methodology for developing multimedia foreign language communicative competence in secondary school students, emphasizing their readiness and ability for effective intercultural communication and self-development through a five-stage, multi-level system. The implementation of this methodology resulted in significant improvements in students' foreign language proficiency, intercultural communication skills, and their ability to effectively use multimedia tools for self-directed learning and collaboration.